2020
DOI: 10.1515/jpm-2019-0391
|View full text |Cite
|
Sign up to set email alerts
|

Short-term neurological improvement in neonates with hypoxic-ischemic encephalopathy predicts neurodevelopmental outcome at 18–24 months

Abstract: ObjectivesTo evaluate the association of short-term neurological improvement until day of life 4 in neonates with hypoxic-ischemic encephalopathy (HIE) receiving therapeutic hypothermia (TH) with neurodevelopmental outcome at 18–24 months.MethodsThis is a retrospective analysis of prospectively collected data of 174 neonates with HIE registered in the Swiss National Asphyxia and Cooling Register between 2011 and 2013. TH was initiated according to national guidelines, and Sarnat staging was performed daily. Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
10
1
2
Order By: Relevance
“…These data suggest that therapeutic hypothermia was most beneficial in a subset of infants who were larger and more likely to have had acute complications during labour rather than infants who were smaller and more likely to have had repetitive hypoxic insults in labour 10. Consistent with this interpretation, a recent study showed that perinatal sentinel events were associated with less severe brain injury on MRI after treatment with therapeutic hypothermia, and improved motor and language outcomes at 18–36 months 11…”
mentioning
confidence: 76%
“…These data suggest that therapeutic hypothermia was most beneficial in a subset of infants who were larger and more likely to have had acute complications during labour rather than infants who were smaller and more likely to have had repetitive hypoxic insults in labour 10. Consistent with this interpretation, a recent study showed that perinatal sentinel events were associated with less severe brain injury on MRI after treatment with therapeutic hypothermia, and improved motor and language outcomes at 18–36 months 11…”
mentioning
confidence: 76%
“…SS is the predominant tool for infant qualification for TH [14], whereas the TS is popular in resource-limited settings, and used as adjunct to SS to confirm NE grading or as a qualifying factor for TH [15, 16]. Short-term improvement in SS or TS are predictive of long-term outcomes [17, 18], and efforts are being made to further refine SS criteria [6].…”
Section: Neurological Exammentioning
confidence: 99%
“…About 15–25% of these newborns die in the neonatal period, up to 25% of survivors develop neurological deficits, and 10–30% have retarded psychomotor development [ 4 , 5 ]. Studies analyzing the long-term consequences in preschool children after perinatal asphyxia have shown that cerebral palsy develops in 5.5–52% [ 6 , 7 , 8 , 9 ], severe disability in 11–19% [ 6 ], various motor impairments in 1.3–40% [ 2 , 8 , 9 , 10 ], hearing loss in 2–20% [ 6 , 9 , 10 ], vision defects in 1.8–40% [ 6 , 9 , 11 ], speech disorders in 4.2–21% [ 6 , 7 , 8 ], epilepsy in 13%, and cognitive impairment in 31% [ 1 , 2 , 12 ].…”
Section: Introductionmentioning
confidence: 99%